2013
DOI: 10.1016/j.neulet.2013.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of bacteria by olfactory ensheathing cells and Schwann cells

Abstract: Opportunistic bacterial infections of the nasal cavity could potentially lead to infection of the brain if the olfactory or trigeminal nerves are colonised. The olfactory nerve may be a more susceptible route because primary olfactory neurons are in direct contact with the external environment. Peripheral glia are known to be able to phagocytose some species of bacteria and may therefore provide a defence mechanism against bacterial infection. As the nasal cavity is frequently exposed to bacterial infections, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 22 publications
2
64
0
Order By: Relevance
“…In the primary olfactory nerve, OECs are the principal phagocytic cells and macrophages are largely excluded even after injury (53). OECs can phagocytose bacteria in vitro (54)(55)(56). We did not investigate invasion of the central nervous system in the present study, but our data demonstrate a tropism of B. pseudomallei for the OM and a defensive reaction by OECs to the bacteria, which supports these previous findings.…”
Section: Discussionsupporting
confidence: 87%
“…In the primary olfactory nerve, OECs are the principal phagocytic cells and macrophages are largely excluded even after injury (53). OECs can phagocytose bacteria in vitro (54)(55)(56). We did not investigate invasion of the central nervous system in the present study, but our data demonstrate a tropism of B. pseudomallei for the OM and a defensive reaction by OECs to the bacteria, which supports these previous findings.…”
Section: Discussionsupporting
confidence: 87%
“…We and others have shown that olfactory glia, olfactory ensheathing cells (OECs), play an essential role in preventing microbial invasion of the olfactory nerve by phagocytosing microorganisms (2,3). The glia of the trigeminal nerve are Schwann cells, which are also phagocytic and remove debris after peripheral nerve injury as well as at least some types of bacteria (3,4).…”
mentioning
confidence: 99%
“…The glia of the trigeminal nerve are Schwann cells, which are also phagocytic and remove debris after peripheral nerve injury as well as at least some types of bacteria (3,4). Thus, glial cells in the nerves that innervate the nasal cavity constitute potentially critical defenses against microbial invasion of the brain.…”
mentioning
confidence: 99%
“…Glial cells of the peripheral nervous system have phagocytic properties, being involved in protection from infection with different bacterial species. The nose is usually exposed to infections with different pathogen germs, which may affect also the fibers of the trigeminal and olfactory nerves found in the nasal cavity 14 . The olfactory nerve may be a more susceptible route because primary olfactory neurons are in direct contact with the external environment.…”
Section: The Role Of the Oecs In Olfactory Systemmentioning
confidence: 99%
“…The olfactory nerve may be a more susceptible route because primary olfactory neurons are in direct contact with the external environment. It was shown that olfactory ensheathing cells and Schwann cells are involved in responding to the bacterial invasion, human OECs being able to phagocyte E. coli 14 .…”
Section: The Role Of the Oecs In Olfactory Systemmentioning
confidence: 99%